Implementation of Independent Learning Curriculum in the Learning of Islamic Religious Education at SMAN 3 Batusangkar - Zulfi, Trisna; Khairat, Annisaul (EDUMALSYS Journal of Research in Education Management, 2023)
Freedom to learn is one of the alternative curriculum choices chosen by the education unit. The independent learning curriculum provides leeway and convenience for educators to implement quality and in-depth learning, according to what students need. The most important thing in this curriculum is to provide a place and freedom for students to develop the abilities that students have in order to get the desired educational achievements. This article was made intending to find out the way PAI teachers do in implementing the independent learning curriculum. This research was conducted at SMAN 3 Batusangkar, with the research target of PAI subject teachers. The researcher uses a descriptive qualitative method with a field study approach. The techniques used to collect data in this study are observation, interviews, and reviewing relevant articles in the direction of the study being studied. This research resulted in PAI teachers planning independent learning curriculum learning, carrying out the learning process by applying the MERDEKA path, and PAI teachers conducting learning evaluations. Therefore, it can be concluded that the implementation and application of the independent learning curriculum in PAI learning is going well and hopes to achieve national education goals.